Pyrrole Carboxamide Binol Conjugates: Chiral Receptors for Chemical Inversion of L-amino Acids to D- amino Acids - Velmurugan, K.; Tang, Lijun; Prabhu, J.; Nandhakumar, R. (Progress in Chemical Science Research Vol. 5, 2022)
The chemical inversion of L-amino acids to D-amino acids has been studied using four pyrrole carboxamide binol conjugates 1–4 as Chirality Conversion Reagent’s (CCR’s). This method involves the formation of a Schiff base type imine with a resonance-assisted hydrogen bond (RAHB), which increases the acidity of the proton. The additional hydrogen bonds between the amino acids and the heterocylic moiety of the pendant groups further stabilize the molecule. The conversion efficiency of all the pyrrole carboxamine based receptors 1–4 was found to be comparable with those of the receptors reported earlier.